2020
DOI: 10.3389/fphys.2020.586290
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Adult Kidney Disease: Importance of Fetal Environment

Abstract: The Barker hypothesis strongly supported the influence of fetal environment on the development of chronic diseases in later life. Multiple experimental and human studies have identified that the deleterious effect of fetal programming commonly leads to alterations in renal development. The interplay between environmental insults and fetal genome can induce epigenetic changes and lead to alterations in the expression of renal phenotype. In this review, we have explored the renal development and its functions, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…Our team previously reported that IUH could result in long-lasting damage in the brain of offspring ( 1 ). Increasing evidence validated the theory of fetal origins of adult disease and that development of cardiovascular disease in adulthood might be associated with intrauterine insults ( 2 4 ). A study in rats revealed that antenatal hypoxia could also increase the severity of heart damage after ischemia-reperfusion injury in offspring ( 5 ).…”
Section: Introductionmentioning
confidence: 87%
“…Our team previously reported that IUH could result in long-lasting damage in the brain of offspring ( 1 ). Increasing evidence validated the theory of fetal origins of adult disease and that development of cardiovascular disease in adulthood might be associated with intrauterine insults ( 2 4 ). A study in rats revealed that antenatal hypoxia could also increase the severity of heart damage after ischemia-reperfusion injury in offspring ( 5 ).…”
Section: Introductionmentioning
confidence: 87%
“…It is hypothesized that these adaptations are made in an attempt to confer the offspring with a selective advantage in the anticipated postnatal environment [ 4 ]. Studies have shown that a range of fetal and neonatal adaptations are made in response to such factors, resulting in physiological manifestations such as reduced muscle fiber and cardiomyocyte proliferation [ 5 ], reduced pancreatic β-cell proliferation [ 6 ] and reduced kidney nephron deposition [ 7 ]. Whereas these in utero adaptations may confer on the offspring the opportunity of reaching sexual maturity and passing on their own genes to the next generation, their long-term consequences increase an individual’s predisposition toward adult ill health.…”
Section: Introductionmentioning
confidence: 99%
“…54 More recent studies have confirmed previous data regarding the role of an adverse fetal environment on kidney maldevelopment, leading to changes in renal phenotypes, with consequences on renal structure and metabolism, including modifications in the renal-angiotensin system and its components. 55…”
Section: Fetal Programming Of Kidney Diseasesmentioning
confidence: 99%